Identification of suitable soils for cultivation of pomegranate (Punica granatum) cv Ganesh - MARATHE, R A; SHARMA, JYOTSANA; BABU, K DHINESH (The Indian Journal of Agricultural Sciences, 2016)
An experiment was conducted during 2008-13 to study the performance of pomegranate (Punica granatum L) cv. Ganesh with respect to changes in soil properties, plant growth, fruit yield and disease incidence on the plants grown under different soil types. After five years of experimentation, soil pH and organic carbon was increased while calcium carbonate content decrease in most of the soils. Plants grown on heavy textured soil have better macro-nutrient uptake, leaf chlorophyll content and vigorous plant growth compared to light textured soil. Fruit yield was highest in the plants grown on clayey soils having 30 cm depth. Plant growth and fruit yield were drastically reduced with the increase in depth of clayey soil (90 and 120 cm). Better quality fruits were produced on the plants grown in gravelly, sandy loam texture soil having depth of 60 cm and even in the plants grown on weathered rock only. Incidence and severity of bacterial blight and wilt disease was higher in the plants grown on clay textured soils compared to light textured soils.